Att organisera för musiklärares professionella utveckling – om identitetsformation och olika praxisgemenskaper - Ferm Thorgersen, Cecilia (Högre utbildning, 2011)
In 2007 the Swedish government decided to put resources in a project that offered active teachers to develop disciplinary and pedagogical competence through doctoral studies. Among ten others the Royal College of Music in Stockholm succeeded with their application and got the chance to educate 10 music teachers from the compulsory school towards a “half” PhD exam, that is called a Licentiate exam in Sweden. The teachers come from all of Sweden and are registered at one of five participating higher music education institutions. At the same time they work for 20 % in their ordinary schools. The common education is organized as courses and in virtual meeting rooms of different kinds. The motive for that is that the teachers are participating in several communities of practice at the same time, aiming to develop as researching practicing teachers in a broad way. In a developing research project the growing of the teachers – eg identity development and professional learning - is followed, guided by the following questions: What becomes the task for higher education when the teachers are taking part in a PhD education at the same time as they work, and are expected to go back to their ordinary work in schools? How can a research school be organized in as a developing learning system where individual experiences have possibility to be shared by others? What are the possibilities for good learning and identity development, and which are the challenges? How can learning trajectories between the research school, the research communities and the everyday practice seen as communities of practice, be encouraged? What authentic questions are engaging the teachers and how do they develop in the social interplay? The methods used are teachers’ continually encouraged written reflections and documented group discussions.